Parechovirus infection as a cause of necrotising enterocolitis in a premature neonate. Issue 11 (23rd November 2020) - Angley, Eleanor; Thomas, Niranjan; Kua, Eugene; Rasheed, Asiyath
Abstract : Parechovirus is becoming increasingly recognised as a cause of morbidity in the neonatal population. It is widely known to cause sepsis, encephalitis and myocarditis. We report a case of parechovirus as a possible cause of necrotising enterocolitis in a premature neonate. The infant, who was born at 28 weeks' gestation, deteriorated at 1 month of life with fever and abdominal distension and had evidence of intramural bowel gas on imaging. Parechovirus was subsequently isolated from naso-oropharyngeal and rectal swabs, and he was managed medically with antibiotics and cessation of enteral feeds.